Development of a RNA-Seq based prognostic signature for colon cancer. (15th March 2021) - Bartlett, Bjarne; Zhu, Yong; Menor, Mark; Khadka, Vedbar S.; Zhang, Jicai; Zheng, Jie; Jiang, Bin; Deng, Youping
RNA-Seq data has recently been used to successfully develop prognostic signatures to predict cancer patients who will have a worse prognosis. We designed a study to ascertain whether a prognostic model, based on RNA-Seq data, would have clinical utility for predicting survival in patients with colon adenocarcinomas (COAD). Of particular interest are early stage COAD patients, for whom the benefits of adjuvant therapy are unclear. High-risk patients predicted by our 5-gene, RNA-Seq signature had significantly shorter survival in both the training (p = 0.00) and test (p = 0.003) cohorts. Here we present an RNA-Seq prognostic signature that can identify high-risk COAD patients with shorter survival. This signature would have clinical utility as part of an RNA-Seq screening program, particularly for identifying early stage COAD patients who could be recommended adjuvant therapy after resection based on the results of this prognostic signature.